1989
DOI: 10.1097/00004032-198910000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of Cs Absorption and Retention in Man

Abstract: One of the consequences of the Chernobyl reactor accident in 1986 was a comparatively high contamination of foodstuffs in Southern Federal Republic of Germany. In order to test radioecological models predicting the radiological consequences of such accidents, several thousand measurements were performed to determine Cs body burdens in members of the public. For the interpretation of these data and as a contribution to the improvement of the available database on the biokinetics of Cs isotopes in humans, we fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
3

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 2 publications
2
15
0
3
Order By: Relevance
“…These results are in agreement with those described by Henrichs et al (1989) who published biological half-time values ranging from 45-210 d, with an average value of 90 ? 50 d in people.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in agreement with those described by Henrichs et al (1989) who published biological half-time values ranging from 45-210 d, with an average value of 90 ? 50 d in people.…”
Section: Discussionsupporting
confidence: 93%
“…Henrichs et al (1989) found an average value equal to 60 d (ranging from 48-86 d). Schwarz and Dunning (1982) reported an average value equal to 65 d (ranging from 30-141 d) but did not find a significant statistical correlation (JJ < 0.05) between biological half-time and body weight.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is generally accepted that Cs ingested as soluble Cs is well absorbed in the gastrointestinal tracts of humans and animals. Results from controlled studies on human subjects indicate that orally administered soluble 137 Cs is rapidly and almost completely absorbed . Furthermore, radioactive Cs in foodstuffs is equally available for absorption in humans and animals .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies (22,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) have addressed the bioavailability and bioaccessibility of radioactive Cs in soils and dietary sources (Table IV). It is generally accepted that Cs ingested as soluble Cs is well absorbed in the gastrointestinal tracts of humans and animals.…”
Section: Extractability and Bioaccessibility Of Radioactive Csmentioning
confidence: 99%